2017
DOI: 10.1038/s41467-017-01958-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for causal top-down frontal contributions to predictive processes in speech perception

Abstract: Perception relies on the integration of sensory information and prior expectations. Here we show that selective neurodegeneration of human frontal speech regions results in delayed reconciliation of predictions in temporal cortex. These temporal regions were not atrophic, displayed normal evoked magnetic and electrical power, and preserved neural sensitivity to manipulations of sensory detail. Frontal neurodegeneration does not prevent the perceptual effects of contextual information; instead, prior expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
119
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(143 citation statements)
references
References 80 publications
14
119
3
Order By: Relevance
“…The effect is localized in a left fronto-central cluster of electrodes, supporting the claim that top-down sensorimotor predictions can exert a functional contribution to the hierarchical generative models underlying speech perception (Cope et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…The effect is localized in a left fronto-central cluster of electrodes, supporting the claim that top-down sensorimotor predictions can exert a functional contribution to the hierarchical generative models underlying speech perception (Cope et al, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…We interpret these as bottom–up connections in agreement with Schoffelen et al (), who found using granger causality connections originating from temporal areas to peak also at the alpha frequency range. Similarly, Cope et al () demonstrated causal connections from temporal to frontal areas in alpha band in a speech perception task. The relatively early time window (0–300 ms) and the stronger PLVs within the alpha band for the LP condition further supports the view of bottom–up information transfer.…”
Section: Discussionmentioning
confidence: 82%
“…Using transfer entropy, Park et al () showed top–down information transfer from left frontal areas to the auditory cortex in language processing. In addition, Cope et al () recently demonstrated a causal connection from the left frontal to the superior temporal area within beta band in predictive speech processing. Given the established role of the prefrontal and orbitofrontal cortex in higher order language comprehension (Halgren et al, ; Lau et al, ), our observation of larger PLVs for LP in the beta band between the left LOF and STG may represent a top–down role, in line with Lewis and Bastiaansen's model (Lewis & Bastiaansen, ).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, both univariate and multivariate logistic regression analyses revealed a higher occurrence of frontal lesions in the MSD group, indicating that frontal lesions are another important independent risk factor for PD-associated MSD. This is could also explain our speculation that PD patients in the MSD group were more prone to cognitive impairment since frontal lesions have been reported as a risk factor for the development of cognitive dysfunction [35][36][37][38]. Additionally, the higher occurrence of frontal lesions in the MSD group might also be attributed to a lack of sufficient plastic repair in some cortical areas following PD, especially in the frontal lobe, a well-known key area for central modulation during speech motor processing.…”
Section: Discussionmentioning
confidence: 87%